Design Method of Improving NGWN（Ⅱ） Efficiency and Carrying Capacity by Using Low-loss and Asymmetrical Gear - Wang Panpan; Qin Datong (Jixie chuandong)
Aiming at the low efficiency and low carrying capacity of NGWN（Ⅱ） planetary transmission,a design method which improve the efficiency and carrying capacity of the system by using low-loss and asymmetric gears is given. The efficiency influenced by contact ratios and the strength influenced by pressure angles and profile-shift coefficient are studied. On this basis,an optimization model aimed at highest efficiency and power density is described,which is subject to the conditions such as teeth,interference and strength. The research results show that the design method and the optimized design parameters can improve the transmission efficiency and carrying capacity of the system effectively.